Development and Performance Evaluation of a Cassava Mash Pulverizing-Cum-Sieving Machine - O., Oladimeji A.; J., Fawohunre A.; G., Olajide O. (Local Engineering, 2025)
Cassava (Manihot esculenta) remains a key staple crop in Nigeria, yet its post-harvest processing continues to face inefficiencies due to manual methods. This study aimed to design, fabricate, and evaluate the performance of a cassava mash pulverizing-cum-sieving machine to address issues of human drudgery, low throughput, and contamination. The machine comprises a hopper, pulverizing chamber, rotary sieve, electric motor, and support frame. Operational testing was carried out at three speeds: 400, 500, and 600 rpm. Results indicated improved sifting efficiency and capacity, with design parameters tailored for durability, portability, and simplicity. This dual-purpose machine demonstrates potential for local cassava processors in Nigeria to enhance productivity and product quality.